2021
DOI: 10.1186/s12889-021-10415-6
|View full text |Cite
|
Sign up to set email alerts
|

Poor linkage to care for HIV-positive OVC with disabled caregivers: a longitudinal study in Tanzania

Abstract: Background Despite extensive efforts to scale up counseling and testing services and care and treatment clinics (CTCs) in Tanzania, linkage between points of diagnosis and CTCs remains low. Studies have looked at barriers such as lack of trained health providers, poor referral system, economic costs or distance to health facilities, but fewer assessed the association between caregivers’ vulnerability such as disability and linkage of orphans and vulnerable children (OVCs) in their care to healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…These explanations must be substantiated with additional research, perhaps requiring qualitative or mixed methods. Our findings suggest the lower odds of HIV+ status among OVC in households <$30 may be attributable to healthcare accessibility issues for extremely poor OVCs and the resulting inability to get diagnoses; however, this was inconsistent with the Tanzania study that found that OVC in a lower socioeconomic status ( 34 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These explanations must be substantiated with additional research, perhaps requiring qualitative or mixed methods. Our findings suggest the lower odds of HIV+ status among OVC in households <$30 may be attributable to healthcare accessibility issues for extremely poor OVCs and the resulting inability to get diagnoses; however, this was inconsistent with the Tanzania study that found that OVC in a lower socioeconomic status ( 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings of the higher proportion of HIV-negative OVC in the parent/guardian group that were themselves HIV+ are noteworthy, and several explanations can be proposed as follows: ( 1 ) HIV+ parents/guardians may have had better knowledge and skills to prevent their children or OVC from HIV transmission; ( 2 ) When extended families need to place an orphan or vulnerable child with someone other than their parents, the extended family may choose an HIV-negative parent/guardian who likely has some combination of more resources, better health, and less vulnerability vs. an HIV+ person; ( 3 ) HIV+ parents, once they know their status, may decide to not have more children to protect their children from infection and stigmatization ( 32 , 33 ); and ( 4 ) DRC's successful PMTCT program, protecting HIV+ women from giving birth to an HIV infected baby likely plays a key role. These results are consistent with the findings of a recent study conducted in Tanzania and South Sudan regarding the impact of the OVC's caregivers and access to clinical care and support services for HIV+ OVC ( 34 36 ). These explanations must be substantiated with additional research, perhaps requiring qualitative or mixed methods.…”
Section: Discussionsupporting
confidence: 92%
“…Four studies targeted individuals <25 years ( 49 52 ). Seventeen studies targeted linkage to care for HIV treatment among the study population ( 44 , 45 , 50 , 51 , 53 63 ). In addition to HIV linkage to care, two of the studies also had links to healthcare for sexual and reproductive health services (HIV, family planning, and male circumcision ( 55 , 56 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most common strengths among the interventions were conducting a longitudinal follow-up of study participants over time, selecting and assigning participants, and descriptive reporting of the intervention. Weaknesses observed by the majority of the studies were the lack of acknowledgment of the participation rate ( 44 , 45 , 50 , 51 , 54 63 ), description of the non-participant ( 44 , 45 , 50 , 51 , 53 61 ), and the quality of life ( 44 , 45 , 50 , 51 , 53 63 ). Attrition was mentioned in two studies but not analyzed ( 45 , 54 ); only one study examined the attrition rate ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation